Smart and Active Food Packaging: Insights in Novel Food Packaging - Ahari, Hamed; Soufiani, Solmaz P. (Frontiers in Microbiology, 2021)
The demand for more healthy foods with longer shelf life has been growing. Food packaging as one of the main aspect of food industry play a vital role in meeting this demand. Integration of nanotechnology with food packaging systems revealed promising promotion in food’s shelf life by introducing novel food packaging systems (FPS). In this review paper, different aspect of FPS including common classification, designed functionalities, employed nanotechnologies and the used biomaterials have been discussed. According to our survey, FPS can be classified as Active Food Packaging (AFP) and Smart Food Packaging (SFP) systems. The functionality of both systems can be manipulated by employing nanotechnologies, such as metal nanoparticles and nanoemulsions, and appropriate biomaterials like synthetic polymers, biomass-derived biomaterial. “Degradability and antibacterial” and “Indicating and scavenging” are the well-known functions for AFP and SFP respectively. Combination of them as a multifunctional FPS is the main purpose to not only increase foods shelf life but also produce environmental friendly packaging. To sum up, although many research has been carried out in this aim, but there are still challenges like human life hazards which need more studies to reach the best FPS.